2015
DOI: 10.1016/j.difgeo.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Classification of proper biharmonic hypersurfaces in pseudo-Riemannian space forms

Abstract: In this paper, we give some examples of proper biharmonic hypersurfaces in de Sitter space S n+1 q (c) and anti-de Sitter space H n+1 q (c), and prove a classification theorem of nondegenerate proper biharmonic hypersurfaces with diagonalizable shape operator and at most two distinct principal curvatures in pseudo-Riemannian space forms N n+1 q (c).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Now we give a complete classification of pseudo-Riemannian hypersurfaces with at most two distinct principal curvatures in a pseudo-Riemannian space form, which improves the classifications given in [17]. (C) with diagonalizable shape operator that has at most two distinct principal curvatures is a part of the following…”
Section: )mentioning
confidence: 67%
See 3 more Smart Citations
“…Now we give a complete classification of pseudo-Riemannian hypersurfaces with at most two distinct principal curvatures in a pseudo-Riemannian space form, which improves the classifications given in [17]. (C) with diagonalizable shape operator that has at most two distinct principal curvatures is a part of the following…”
Section: )mentioning
confidence: 67%
“…As an immediate consequence, we have the following corollary, which was stated in [17] without a proof. Proof.…”
Section: Biharmonic Pseudo-riemannian Submanifolds Of Pseudo-riemannimentioning
confidence: 71%
See 2 more Smart Citations
“…Sasahara in [11] considered biharmonic hypersurfaces M 2 r of S 3 1 ðcÞ and proved that it must be minimal when r = 0, but may not when r = 1. Investigators studied biharmonic hypersurfaces with at most two distinct principal curvatures in S n+1 s ðcÞ whose shape operator is diagonalizable in [6,8] and showed that such hypersurface M n s−1 is minimal, but the hypersurface M n s may not. Naturally, there is a question as to whether any biharmonic hypersurface M n s−1 in de Sitter space S n+1 s ðcÞ is minimal.…”
Section: Introductionmentioning
confidence: 99%